Pickering Emulsions Stabilized by Tea Water-Insoluble Protein Nanoparticles From Tea Residues: Responsiveness to Ionic Strength - Ren, Zhongyang; Chen, Zhongzheng; Zhang, Yuanyuan; Lin, Xiaorong; Weng, Wuyin; Li, Bin (Frontiers in Nutrition, 2022)
Tea water-insoluble protein nanoparticles (TWIPNs) can be applied to stabilize Pickering emulsions. However, the effect of ionic strength (0–400 mmol/L) on the characteristics of Pickering emulsions stabilized by TWIPNs (TWIPNPEs) including volume-averaged particle size (d4,3), zeta potential, microstructure and rheological properties is still unclear. Therefore, this work researched the effect of ionic strength on the characteristics of TWIPNPEs. The d4,3 of TWIPNPEs in the aquatic phase increased with the increase in ionic strength (0–400 mmol/L), which was higher than that in the SDS phase. Furthermore, the flocculation index of TWIPNPEs significantly (P < 0.05) increased from 24.48 to 152.92% with the increase in ionic strength. This could be verified from the microstructure observation. These results indicated that ionic strength could promote the flocculation of TWIPNPEs. Besides, the absolute values of zeta potential under different ionic strengths were above 40 mV in favor of the stabilization of TWIPNPEs. The viscosity of TWIPNPEs as a pseudoplastic fluid became thin when shear rate increased from 0.1 to 100 s−1. The viscoelasticity of TWIPNPEs increased with increasing ionic strength to make TWIPNPEs form a gel-like Pickering emulsion. the possible mechanism of flocculation stability of TWIPNPEs under different ionic strengths was propose. TWIPNs adsorbed to the oil-water interface would prompt flocculation between different emulsion droplets under the high ionic strength to form gel-like behavior verified by CLSM. These results on the characteristics of TWIPNPEs in a wide ionic strength range would provide the theoretical basis for applying Pickering emulsions stabilized by plant proteins in the food industry.